Protein deregulation associated with breast cancer metastasis. Issue 4 (August 2015) - Chan, Ka Kui; Matchett, Kyle B.; McEnhill, Paul M.; el H, Dakir; McMullin, Mary Frances; El-Tanani, Yahia; Patterson, Laurence; Faheem, Ahmed; Rudland, Philip S.; McCarron, Paul A.; El-Tanani, Mohamed
Highlights Distant metastases are usually more aggressive and malignant outgrowth can cause serious complications, rendering effective therapy complicated. These findings may provide insights into the development of more promising markers for diagnosis and therapeutic strategies. Ran, in the primary tumors may allow prediction of the likelihood of relapse and derivation of more effective treatment regimens.